Pemanfaatan Aplikasi Let's Read dalam Meningkatkan Literasi Membaca Siswa Kelas 2 Sekolah Dasar - Nurhabibah Nurhabibah; Mhmd Habibi; Nursalim Nursalim; Risnawati Risnawati (Ideas Publishing, 2023)
This research was conducted in grade 2 of elementary school and was motivated by a lack of reading literacy among elementary school students. The purpose of this study was to determine the effect of using the Let's Read application on reading literacy of 2nd grade elementary school students. This study used quantitative research which in this study required 2 classes, namely class 2A and class 2B with a description of class 2A as the experimental class and class 2B as the control class. The reading literacy questionnaire is the instrument used in this study. Data processing shows that the use of the Let's Read application has a significant impact on reading literacy among second grade students.